Exploring the land use and land cover change in the period 2005–2020 in the province of Errachidia, the pre-sahara of Morocco - Karmaoui, Ahmed; Ben Salem, Abdelkrim; El Jaafari, Samir; Chaachouay, Hassan; Moumane, Adil; Hajji, Lhoussain (Frontiers in Earth Science, 2022)
The study investigates the land use and land cover (LULC) change under the climate change (CC) and anthropogenic effects in Errachidia province (Pre-Saharan of Morocco) in the period 2005–2020. To this end, remote sensing (RS) tools such as LULC, the normalized difference vegetation index (NDVI), the normalized difference water index (NDWI), the Enhanced Vegetation Index (EVI), Gravity Recovery and Climate Experiment (GRACE) satellite data, and precipitations were processed and combined. The monitoring of LULC over this period reveals different changes under CC and anthropogenic impact in this area. Generally, for water bodies, two trends can be observed, an increasing trend since 2006 and a decreasing trend from 2011 to the present. However, an increasing trend was recorded for the urban-and-built-up-lands and the grasslands categories. NDVI, NDWI, and EVI showed three major peaks recorded in the same periods (in 2007, 2009, and 2015). In terms of water storage, three phases were found. The first depicted the lowest groundwater quantities with a decreasing trend, which corresponds to a pe-riod of drought and/or human pressure. The second phase, the most important that recorded the greatest storage of water while the third phase corresponds to low storage with a decreasing trend. LULC of croplands reveals a slightly increasing trend from 2012 to 2020, which shows an orientation to an extension of crops mainly of date palm encouraged by government programs. A strong correlation between the seasonal NDVI and water storage using GRACE-Data for the period was found. In the end, recommendations on the adaptation to CC were proposed. The findings demonstrate that RS techniques are useful tools to detect hydrological droughts, ob-serve, and conserve land resources. In arid areas such as Errachidia, the solution lies in rational-izing the use of water resources protecting them from uncontrolled anthropogenic events, which may alleviate the pressure. To support local sustainable development, environmental scientists and decision-makers may use the outputs of this study.